Ghosts in the Machine: Informality, Implementation Failure, and the Active Destruction of Trust in Nigeria’s Subsidy Reform - Gana, Idrees Mahmud; Ogaji, Tijani Adamu; Augustine, Baba Theophilus (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
The 2023 removal of Nigeria's fuel subsidy, which was supposed to free up fiscal resources for development, resulted in dramatic price hikes, inflation, and widespread popular anger. This paper contends that the reform's failure arises not only from technical or planning shortcomings, but also from the ubiquitous effect of informal institutions on policy implementation. Fuel merchants, bureaucratic gatekeepers, and political elites formed networks that influenced pricing, distribution, and palliative measures, shifting benefits and undercutting compensatory efforts. Using a qualitative single-case study and informal institutions theory, the analysis shows how these individuals deliberately undermine formal changes, resulting in active trust destruction, in which citizens regard policy failure as deliberate rather than incidental. The findings indicate that ad hoc and opaque relief measures enhance distrust, limiting the legitimacy gains of reform. The report concludes that without institutionalised transparency, effective monitoring, and regular compensation, Nigerian subsidy reforms will continue to fail, growing public scepticism and jeopardising economic and political stability.